The Development of Cooperative Learning Model of STAD Type Based Learning Materials to Improve Students Collaborative Thinking Skills - Supratiningsih Supratiningsih; Suparti Suparti; Dafik Dafik; O A Safiati (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
This study aimed at developing STAD type-based cooperative learning materials to improve students’ collaborative thinking skill. The study used Research and Development (R&D) method by Thiagarajan which consists of four stages: define, design, develop, and disseminative. The developed materials included RPP, LKPD and THPD. The validity result of the pre test and post test showed that the materials fulfilled valid criteria. The validity test was done using SPSS 14 program and the results showed that Sig. (2- tailed) value was lower than (≤) 0,05 and thus considered valid, and the Alpha Croncbrach was higher than (≥) 0,60 which made it considered reliable. The validity test for the results of practicality observation test showed a result of very practical and the effectivity results were gained from one-sample t-test that was by comparing the pre-test and post-test scores, which showed that the students and teacher’s activity in the limited classroom fulfilled the criteria practical and effective. The STAD type cooperative learning materials developed in this study had significant effects on students’ collaborative thinking skill in solving addition and subtraction problems. Based on the table of descriptive results for paired sample t-test, it can be concluded that there was differences on the average score of 85 > 71,67 and Sig.(2-tailed) = 0,000 which means Sig. < 0,05. Based on those results, it can be concluded that H0 was rejected and Ha was accepted which means that the learning results between pre-test and post-test were different.